Penerapan Layanan Bimbingan Kelompok Dengan Metode Relaksasi Untuk Mengatasi Kecemasan Lansia - Nofria Rahmadani; Kusnadi Kusnadi; Lena Marianti (Scidacplus, 2023)
Old age brings physical, psychological, and bodily changes. The decline in physical strength occurs during the elderly phase, causing difficulties and anxiety. Group counseling services with a relaxation method help the elderly overcome anxiety and achieve a happy elderly phase. Therefore, a research titled